Application of Model Predictive Control to Reduce The Vibrationof Two Connected Buildings - Sutrisno Sutrisno; Dita Anies Munawarroh (MATEMATIKA, 2016)
In this paper, model predictive control (MPC) will be applied to reduce the vibration of two connected buildings (TCB) that can be caused by, for example, seismic activities. Mathematical model of TCB can be formulated as a linear time invariant state space equation. The state of this plant is the displacement of each building measured from the origin. We will regulate or bring the state to the origin as fast as possible with optimal control input. This optimal control input will be determined using MPC. We give a numerical simulation to observe how this control method is working. From the simulation result, MPC reduces the vibration of TCB and bring the displacement of each building to the origin faster than uncontrolled system.